2016
DOI: 10.1016/j.ijgo.2015.08.026
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of abdominal binders for the management of postoperative pain and distress after cesarean delivery

Abstract: Postoperative pain and distress scores after cesarean delivery were not affected by abdominal binders. ClinicalTrials.gov:NCT02129894.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 15 publications
2
28
2
Order By: Relevance
“…The present randomized controlled trial investigated the effect of abdominal binders on pain, distress, and hemorrhage among women who had undergone non‐emergency cesarean delivery. To the best of our knowledge, few studies have evaluated these effects . The results demonstrated greater decreases in pain and distress among patients who used abdominal binders after cesarean delivery, and reduced blood loss.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present randomized controlled trial investigated the effect of abdominal binders on pain, distress, and hemorrhage among women who had undergone non‐emergency cesarean delivery. To the best of our knowledge, few studies have evaluated these effects . The results demonstrated greater decreases in pain and distress among patients who used abdominal binders after cesarean delivery, and reduced blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…assessed the effect of abdominal binders on post‐operative pain. Further, a randomized controlled trial by Gillier et al., evaluated VAS scores among 155 patients for 2 days after cesarean delivery; they reported similar VAS scores between patients who did and did not received abdominal binders on both post‐operative days. Conversely, a different study reported a significant reduction in post‐cesarean pain among patients using abdominal binders…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations